2012
DOI: 10.1016/j.rehab.2012.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Patients with complicated Pott's disease: Management in a rehabilitation department and functional prognosis

Abstract: Rehabilitation takes an important place in the medico-surgical management in Pott's disease, to limite or compensate the disabilities and handicap related to this pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Most rehabilitation regimes are best outlined to the patient during inpatient rehabilitation. Both studies examining the effect of inpatient rehabilitation on functional outcomes have demonstrated significant improvement in FIM [20,21]. Regardless whether patients were treated conservatively or surgically in the initial treatment for spinal tuberculosis, neurologically impaired individuals need to undergo retraining and mobilization of their muscles.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most rehabilitation regimes are best outlined to the patient during inpatient rehabilitation. Both studies examining the effect of inpatient rehabilitation on functional outcomes have demonstrated significant improvement in FIM [20,21]. Regardless whether patients were treated conservatively or surgically in the initial treatment for spinal tuberculosis, neurologically impaired individuals need to undergo retraining and mobilization of their muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the mode of initial treatment, all the spinal tuberculosis patients in the chosen studies eventually received rehabilitation management, and Zaoui et al [20] found that the mean of modified Barthel Index (MBI) significantly increased from 75.5 to 92.65 with inpatient rehabilitation after 6 months of diagnosis. Zaoui et al [20] stressed the need for postoperative immobilization with the use of orthoses, either in the form of a corset or cervical collar, when rehabilitation was initiated. This was followed by early and progressive verticalization by physiotherapy that aimed for the prevention of decubitus complications while preserving articular, muscular, trophic, and respiratory functions.…”
Section: Modes Of Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In a review series of 1,997 patients on world literature, the thoracic spine was the most frequent segment involved 20 . Although the thoracic and thoracolumbar spines are involved most commonly, the disease may be seen in any region of the spine 21,22 . Four common sites of infection in the vertebra are more affected; para-discal, central, subligamenteous, just behind the anterior longitudinal ligament of the spine, and appendiceal 23 .…”
Section: Discussionmentioning
confidence: 99%